An Introduction to Information Theory - Pierce, John R. 1910-2002 (Tantor Media, Inc., 2019)
Behind the familiar surfaces of the telephone, radio, and television lies a sophisticated and intriguing body of knowledge known as information theory. This is the theory that has permitted the rapid development of all sorts of communication, from color television to the clear transmission of photographs from the vicinity of Jupiter. Even more revolutionary progress is expected in the future. Beginning with the origins of this burgeoning field, Dr. Pierce follows the brilliant formulations of Claude Shannon and describes such aspects of the subject as encoding and binary digits, entropy, language and meaning, efficient encoding, and the noisy channel. He then goes beyond the strict confines of the topic to explore the ways in which information theory relates to physics, cybernetics, psychology, and art. Mathematical formulas are introduced at the appropriate points for the benefit of serious students. J. R. Pierce worked for many years at the Bell Telephone Laboratories, where he became Director of Research in Communications Principles. An Introduction to Information Theory continues to be the most impressive nontechnical account available and a fascinating introduction to the subject for lay listeners.
Online resource; Title from title page (viewed October 8, 2019)
Keywords: Information theory; Audiobooks; Information Theory; Livres audio; Théorie de l'information; Downloadable audio books